2021
DOI: 10.18261/issn.1892-2686-2021-04-06
|View full text |Cite
|
Sign up to set email alerts
|

Helsesykepleier på hjemmebesøk hos mødre med innvandrerbakgrunn

Abstract: Tiden etter fødsel kan oppleves av mange mødre med innvandrerbakgrunn som en sårbar periode med emosjonelle endringer og usikkerhet i foreldrerollen. Det foreligger lite forskning om hvordan mødre med innvandrerbakgrunn opplever å bli ivaretatt av helsesykepleier på hjemmebesøk etter fødsel. Hensikten med studien er å undersøke mødrenes opplevelser av helsesykepleiers ivaretakelse av deres behov. Studien har et kvalitativt design. Det ble gjennomført individuelle semistrukturerte intervjuer med seks mødre med … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…It was especially important to provide relevant information before a home visit to immigrant parents. This is supported by the findings in a recent study by Jensen and Clancy (2021) among immigrant mothers of new-born children in Northern Norway. These mothers had received limited information about the purpose and content of the PHN's home visits.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…It was especially important to provide relevant information before a home visit to immigrant parents. This is supported by the findings in a recent study by Jensen and Clancy (2021) among immigrant mothers of new-born children in Northern Norway. These mothers had received limited information about the purpose and content of the PHN's home visits.…”
Section: Discussionsupporting
confidence: 85%
“…These mothers had received limited information about the purpose and content of the PHN's home visits. For instance, they did not know that these visits were optional (Jensen & Clancy, 2021 ). Another study indicated that few women preferred a prenatal home visit from the PHN because they had an inadequate understanding of the purpose of this prenatal contact (Olander et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation